High heat flux thermal solution for high power system - Koh, Si Yuh (2016)
With the rapid advancement in technology especially in the microelectronics and semiconductor industry, overheating is a common problem that is faced in this industry as too much heat generated will cause the malfunction of devices. Hence, there is a need to find solutions to remove the heat generated from these systems in order for the devices to function efficiently. Researchers have come up with many solutions to tackle this problem and spray cooling is one of the most potential thermal solution to overcome the high heat flux generated in the systems. In this project, an open loop spray cooling set-up will be utilised. One of the variables in this experiment will be the type of coolant used. As different fluids have different fluid properties embedded in them, an investigation was conducted to observe the effect of different fluid properties in enhancing the heat removal rate from the surface of the heater block. The three chemicals shortlisted to be used in this project were Tween-20, 1-Butanol and Magnesium Sulphate as these three chemicals have been tested from previous studies [6, 24, 31] that they do have the ability to improve the heat transfer. Each chemical was prepared in two concentrations – 100ppm and 1500ppm and were tested for their effectiveness. Another variable was the type of nozzle used – single-nozzle and four-nozzle. Experimental results showed that in the case of the single-nozzle, all three chemicals do produce substantial increase in the heat flux as compared to DI water. In the case of the four-nozzle, the results obtained were not that favourable. For Tween-20 and 1-Butanol, the most favourable results were when 100ppm of the chemical was used and for Magnesium Sulphate, it did not show any improvement in the heat flux compared to DI water. This shows that other than the fluid properties that will affect the cooling performance, there are many other factors such as the pressure drop, spray height and spray velocity that also have an impact on the heat transfer performance. However, due to the constraint of time, the effect of different fluid properties will be focused in this report.